MAPPING OF THE ENVIRONMENT USING MULTISPECTRAL SATELLITE IMAGERY - Potić, Ivan; Šimunić, Vanja (Bulletin of Natural Sciences Research, 2019)
Continuous environmental mapping has never been more necessary because of the fast-paced lifestyle, technology development, climate change. Monitoring changes in the environment has become one of the most important tasks todayto understand those changes and take the necessary measures to coordinate sustainable development with the emerging natural and socio-economic events. Remote sensing combined with cartography gives us the opportunity to obtain current information on the state of the environment and react suitablyin order to reduce damage to a minimum in accordance with sustainable development.